2016
DOI: 10.1177/1753425916681077
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory signaling pathways induced byHelicobacter pyloriin primary human gastric epithelial cells

Abstract: Inflammatory signaling pathways induced by Helicobacter pylori remain unclear, having been studied mostly on cell-line models derived from gastric adenocarcinoma with potentially altered signaling pathways and nonfunctional receptors. Here, H. pylori-induced signaling pathways were investigated in primary human gastric epithelial cells. Inflammatory response was analyzed on chemokine mRNA expression and production after infection of gastric epithelial cells by H. pylori strains, B128 and B128Δ cagM, a cag type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…Previous reports have shown that berberine exerts a clearance effect and reduces gastric inflammation during epithelial cell signalling in H. pylori infection [ 23 ]. Based on this network, the targets associated with epithelial cell signalling are EGFR and CXCL8, which are important responses to H. pylori infection [ 24 26 ]. Helicobacter pylori infection may upregulate the expression of EGFR and CXCL8 through the cell response to epidermal growth factor stimulus (GO 0071364) and the response to bacterial molecules (GO 0002237), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that berberine exerts a clearance effect and reduces gastric inflammation during epithelial cell signalling in H. pylori infection [ 23 ]. Based on this network, the targets associated with epithelial cell signalling are EGFR and CXCL8, which are important responses to H. pylori infection [ 24 26 ]. Helicobacter pylori infection may upregulate the expression of EGFR and CXCL8 through the cell response to epidermal growth factor stimulus (GO 0071364) and the response to bacterial molecules (GO 0002237), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All these markers decreased significantly when cells were treated with AAF/II in the presence of TLR4 antagonist (Figure 4). GRO is a chemokine involved in the recruitment of neutrophils in several bacterial and non-bacterial infections including H. pylori (Tran et al, 2017), E. coli (Lee et al, 2018), B. cereus (Coburn et al, 2018), rhinovirus (Jamieson et al, 2019) and Leishmania (Ronet et al, 2018). Moreover, it has been shown to be associated with neutrophil recruitment mediated by the Th17 response (Fujie et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Cortex magnolia officinalis is another herb that has been proven to have anti-HP activity [ 18 , 20 ]. The activation of the inflammatory signaling pathways plays a crucial role in the pathogenicity of HP [ 21 ]. The inhibition of HP and the suppression of the HP-related inflammatory signaling pathways might be important underlying mechanisms for QHY efficacy.…”
Section: Discussionmentioning
confidence: 99%